Analisis Sistem Katalogisasi di Pepustakaan SMA N 1 Payakumbuh - Metri Arindi (Perpustakaan Nasional RI, 2022)
The school library is a facility and pre-facility to support teaching and learning activities at the school level because the school library is an integral part of the education program at the school level. The school library is designed to meet the information needs of the community in every school environment, especially teachers and students. In the school library there are various collections that must be processed so that they are easy to use by library visitors or users. The things that can be done by librarian is cataloging library materials or collections to facilitate the process of retrieval of information needed by users. Therefore, this study uses descriptive qualitative research methods, in order to be able to describe how the cataloging in the library of SMA N 1 Payakumbuh. From the data and research results, it is known that the activity of cataloging or cataloging has followed and is in accordance with the cataloging system guided by the International Standard Bibliographic Description (ISBD). In the process of cataloging collections or library materials using SLiMS is an convenience for librarians in data management so that it affects the services provided to library visitors or users.